THE INFLUENCE OF SCHOOL CULTURE, JOB SATISFACTION, AND WORK MOTIVATION ON KINDERGARTEN TEACHERS' PERFORMANCE IN PKG AREA III, PIDIE REGENCY - Rahmawati, Dina; Marwan, Marwan; Yanti, Hera (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to determine: (1) the influence of school culture on the job satisfaction of kindergarten teachers in PKG Region III, Pidie Regency, Aceh Province, (2) the influence of school culture on the work motivation of kindergarten teachers in PKG Region III, Pidie Regency, Aceh Province, (3) the influence of school culture on the performance of kindergarten teachers in PKG Region III, Pidie Regency, Aceh Province, (4) the influence of job satisfaction on the performance of kindergarten teachers in PKG Region III, Pidie Regency, Aceh Province, and (5) the influence of work motivation on the performance of kindergarten teachers in PKG Region III, Pidie Regency, Aceh Province. The population in this study were all kindergarten teachers under the auspices of PKG Region III, Pidie Regency, totaling 114 people, with a sample size of 89 people determined using proportional random sampling techniques. This study uses a quantitative approach and path analysis method to test the direct influence between variables. The results of the study indicate that school culture has a direct influence on job satisfaction with a beta coefficient of 0.882 (88.2%), on work motivation of 0.897 (89.7%), and on teacher performance of 0.145 (14.5%). Job satisfaction has a direct effect on teacher performance of 0.116 (11.6%), while work motivation has the most dominant effect on teacher performance with a beta coefficient of 0.945 (94.5%). This finding implies that work motivation is a key factor in improving the performance of kindergarten teachers, which is strengthened by the role of school culture and positive job satisfaction